Research of methods of water additives to fuel in a conventional engine - A. V. Bizhaev (Сельскохозяйственные машины и технологии, 2015)
The main energy source for stationary installations and mobile vehicles is a conventional engine. There are several its requirements: restriction on toxic emissions in the atmosphere and increase of economic indicators, including efficiency. The delivery fuel and water system was offered in the 60th years for these key problems solution. Such system insures process of mixture burning at lower temperature. First of all it causes reduction of nitrogen oxides emission and intensifies the chemical processes leading to increase in the energy received at mixture burning. The water delivery methods were investigated and compared them around each other. It was showed that there are some basic ways of an water additive. It is necessary to investigate them for a complex assessment of the current situation. It was revealed that each method differs in the features which include not only a constructive component, but also a set of the physical and chemical processes considerably influencing on mixture burning process. This research will become the base for receiving empirical indicators when carrying out experiment.